FILM PENDEK ALAT PENGKAJIAN KESEHATAN KELUARGA KHON KAEN UNIVERSITY - Suwarno; Jongudomkarn, Darunee (Universitas Jenderal Achmad Yani Yogyakarta, 2016)
Background:Family health care in family nursing is focused on a holistic health care view. A holistic health carewill be achieved if the family health nursing care is properly executed. The continuing education is appropriate to increase the family health assessment application and understanding. It consists of training programs, which might take advantage of a video as a learning media. Objective:The objective of the study was to produce the KKU FHA tool short movie based on the 3 phases; pre-production, production and post-production. Methods:Five nursing educators reviewed the video and evaluateit with a form in a Likert scale. Result: This video was in MOV format, sized1.12 GB, the picture size was 1280x720, codec H.264, AAC, length of time was 16.53 minutes and could be opened in smartphone andcomputer. The mean score of the evaluation form was 3.6 for the quality of sound and 4.8 for the benefit of the video. The total mean score was 45.8 out of55. Conclusion:The KKU FHA tool short video was appropriate and could be implemented ina try-out or a training program, and couldalsobe developed and improvedto achieve the best quality of sound and picture. Keywords: Family health assessment, KKU FHA Tool, training, short movie